Queen Hereafter : a novel - Schuler, Isabelle (Harper Perennial, 2023)
"Daughter of an ousted king, descendant of ancient druids, Gruoch (GREW-ock), has grown up believing that she will be crowned queen of Alba and reclaim the lands of her Pictish kin, a prophecy seemingly fulfilled by her betrothal to Duncan, the heir-elect. Determined never to be powerless again, she leaves behind her home, her family, and her close friend MacBethad, and travels to the royal seat at Scone to embrace her new position. But Duncan's court is rife with sly words and unfriendly faces, women desperate to usurp her position, and others whose motives are shrouded in mystery. As her coronation approaches, a deadly turn of events forces Gruoch to flee Duncan and the capital. Alone and at the mercy of an old enemy, her hope of becoming Queen all but lost, Gruoch must make a fateful choice: live a long, quiet life in the shadows, or seize vengeance and a path back to the throne" -- Provided by publisher.